2020
DOI: 10.1080/15361055.2020.1718839
|View full text |Cite
|
Sign up to set email alerts
|

Performance Restoration of a Tritium-Aged LaNi4.25Al0.75 Sample

Abstract: The title and author names are listed on this sheet as they will be published, both on your paper and on the Table of Contents. Please review and ensure the information is correct and advise us if any changes need to be made. In addition, please review your paper as a whole for typographical and essential corrections.Your PDF proof has been enabled so that you can comment on the proof directly using Adobe Acrobat. For further information on marking corrections using Acrobat, please visit http://journalauthors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Essentially all the gas from a tritium-aged sample had been released by 600 °C. Later, Staack and James [5] showed that heating a tritium-aged LANA.75 sample to 450 °C moderately restored the performance while heating the sample to 600 °C significantly improved the performance. This improvement between 450 and 600 °C was likely due to the release of the second He-3 peak.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially all the gas from a tritium-aged sample had been released by 600 °C. Later, Staack and James [5] showed that heating a tritium-aged LANA.75 sample to 450 °C moderately restored the performance while heating the sample to 600 °C significantly improved the performance. This improvement between 450 and 600 °C was likely due to the release of the second He-3 peak.…”
Section: Introductionmentioning
confidence: 99%